Initial solution pH value for the construction of a 3D hydroxyapatite via the trisodium citrate-assisted hydrothermal route - Qi, Mei-li; Wang, Wen; Liu, Xiao-Cun; Wang, Xiaoying; Li, Jin; Zhang, Haijun (Frontiers in Chemistry, 2024)
In this study, a trisodium citrate (TSC)-assisted hydrothermal method is utilized to prepare three-dimensional hydroxyapatite (3D HA). Understanding the role of TSC in the preparation of 3D HA crystals may provide valuable methods to design advanced biomaterials. As one of the indexes of solution supersaturation, the initial pH (ipH) value can not only directly affect the nucleation rate, but also affect the growth of HA crystals. In this work, the effect of the ipH on the microstructure, particle size distribution, and specific surface area of the 3D HA is explored. Results showed that the morphology of 3D HA transformed from a bundle to a dumbbell ball and then a dumbbell with an increase in the ipH. A corresponding mechanism of such a structural evolution was proposed, providing inspiration for the fabrication of innovative 3D HA structures with enhanced biological functionality and performance.